(untitled) - Solomon, Michael R. (Boston, 2018)
In this textbook on consumer behaviour the author looks at how the field of marketing is influenced by the actions of consumers and also how we, as consumers, are influenced by marketers. For courses in Consumer Behavior. Beyond Consumer Behavior: How Buying Habits Shape Identity Solomon's Consumer Behavior: Buying, Having, and Being deepens the study of consumer behavior into an investigation of how having (or not having) certain products affects our lives. Solomon looks at how possessions influence how we feel about ourselves and each other, especially in the canon of social media and the digital age. In the Twelfth Edition, Solomon has revised and updated the content to reflect major marketing trends and changes that impact the study of consumer behavior. Since we are all consumers, many of the topics have both professional and personal relevance to students, making it easy to apply them outside of the classroom. The updated text is rich with up-to-the-minute discussions on a range of topics such as "Advertising," "Meerketing," and the "Digital Self" to maintain an edge in the fluid and evolving field of consumer behavior. MyMarketingLab not included. Students, if MyMarketingLab is a recommended/​mandatory component of the course, please ask your instructor for the correct ISBN and course ID. MyMarketingLab should only be purchased when required by an instructor. Instructors, contact your Pearson representative for more information. MyMarketingLab is an online homework, tutorial, and assessment product designed to personalize learning and improve results. With a wide range of interactive, engaging, and assignable activities, students are encouraged to actively learn and retain tough course concepts.
Keywords: Hành vi tiêu dùng,Consumer behavior